1987
DOI: 10.1364/ao.26.001207
|View full text |Cite
|
Sign up to set email alerts
|

Optics of two-stage photovoltaic concentrators with dielectric second stages

Abstract: Two-stage photovoltaic concentrators with Fresnel lenses as primaries and dielectric totally internally reflecting nonimaging concentrators as secondaries are discussed. The general design principles of such two-stage systems are given. Their optical properties are studied and analyzed in detail using computer ray trace procedures. It is found that the two-stage concentrator offers not only a higher concentration or increased acceptance angle, but also a more uniform flux distribution on the photovoltaic cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Therefore for the rays to exit it, aperture must be within the designed acceptance angle of the concentrator. The study on two-stage photovoltaic concentrators with Fresnel lenses as primaries and dielectric totally internally reflecting non-imaging concentrators as secondaries revealed that, higher concentration and more uniform flux distribution on the photovoltaic cell was observed in two-stage concentrator than the point focusing Fresnel lens [51]. Lateral view of a DTIRC [50] VII.…”
Section: Dielectric Totally Internally Reflecting Concentratormentioning
confidence: 96%
“…Therefore for the rays to exit it, aperture must be within the designed acceptance angle of the concentrator. The study on two-stage photovoltaic concentrators with Fresnel lenses as primaries and dielectric totally internally reflecting non-imaging concentrators as secondaries revealed that, higher concentration and more uniform flux distribution on the photovoltaic cell was observed in two-stage concentrator than the point focusing Fresnel lens [51]. Lateral view of a DTIRC [50] VII.…”
Section: Dielectric Totally Internally Reflecting Concentratormentioning
confidence: 96%
“…Figure 6. Side view for basic design of a DTIRC [31] DTIRC as a secondary concentrator has been widely used in various applications such as the pumping of power laser systems [32], concentrated photovoltaic (CPV) [14], and solar thermal application in space [33], [34]. Recently, Cruz-Silva et al [16] reformulate the Ning's formulation of DTIRC [31] to obtain an analytical framework for feasible designs which are easily implemented for computer numerical control (CNC) manufacturing and presented solar flux distribution in Linear Fresnel reflector (LFR) and parabolic through collector (PTC) using DTRIC as secondary concentrator.…”
Section: Dielectric Totally Internally Reflecting Concentrator (Dtirc)mentioning
confidence: 99%
“…This technology offers more open-ended structure for the systems, for example, upward-facing receiver [12] or appropriate heat storage design [13]. Besides, it provides higher concentration ratios [14]- [16] and effective power distribution [12]. The aim of this paper was to review secondary concentrators based on solar concentration and their other characteristics such as advantages, disadvantages, and performance.…”
Section: Introductionmentioning
confidence: 99%
“…When a set of rays hits the front curved surface at the acceptance angle, it is refracted and directed to the exit aperture. Ning et al [82] discussed two-stage photovoltaic concentrators with Fresnel lenses as primaries and dielectric totally internally reflecting nonimaging concentrators as secondaries. The results indicated that two-stage concentrator suggests higher concentration and more uniform flux distribution on the photovoltaic cell than the point focusing Fresnel lens alone.…”
Section: Dielectric Totally Internally Reflecting Concentrator (Dtirc)mentioning
confidence: 99%